β-Cyclodextrin functionalized ionic liquid as high performance liquid chromatography chiral stationary phase for the enantioseparation of natural products and pharmaceuticals / Nurul Yani Rahim - Nurul Yani, Rahim (2017)
The demanding for enantiomerically pure (enantiopure) compounds, especially for pharmaceutical field has been attracting great attention during last decades. Direct enantioseparation by chiral stationary phases (CSPs) using high performance liquid chromatography (HPLC) remains as the most important technique for enantioseparation. The development of novel stable and powerful CSPs is therefore important. The first part of this study involved a facile and reliable preparation of CSPs. Thus, β- cyclodextrin was functionalized with ionic liquids (ILs) namely 1-benzylimidazole (1- BzlIm) and 1-decyl-2-methylimidazole (C10MIm) with tosylate as anion produced β- CD-BIMOTs and β-CD-DIMOTs respectively. β-CD-BIMOTs and β-CD-DIMOTs were attached to the modified silica to obtain the CSPs. The performances of the synthesized CSPs were determined by examining the capability of enantioseparation of selected analytes: flavonoids (flavanone, hesperetin, naringenin and eriodictyol), β- blockers (atenolol, metoprolol, pindolol and propranolol) and Non-steroidal antiinflammatory drug (NSAIDs) (ibuprofen, fenoprofen, ketoprofen and indoprofen). The performance of β-CD-BIMOTs and β-CD-DIMOTs stationary phases was also compared with native β-CD stationary phase. The results indicated that β-CD-BIMOTs stationary phase afforded more favorable enantioseparations than β-CD-DIMOTs and native β-CD based stationary phases. Therefore, the optimization for enantioseparation of selected analytes (flavonoids, β-blockers and NSAIDs) and evaluation of interactions was further investigated on β-CD-BIMOTs stationary phase. The selected flavonoids, flavanone and hesperetin obtained high resolution factor in reverse phase mode. Meanwhile naringenin and eriodictyol attained partial enantioseparation in polar organic mode. In order to understand the mechanism of separation, the interaction of selected flavonoids and β-CD-BIMOTs was studied using spectroscopic methods which are 1H NMR, NOESY and UV/Vis spectrophotometry. The result for enantioseparation of selected β-blockers, propranolol and metoprolol showed good enantioresolution compared to atenolol and pindolol. The results suggested that the lipophilic property and the structure of propranolol and metoprolol that enable the formation of inclusion complex contribute to better enantioseparation. This observation was proven by 1H NMR and NOESY of β-CD-BIMOTs/β-blockers. The effect of the types and variation of mobile phase composition on enantioseparation of NSAIDs was also studied on β- CD-BIMOTs CSP. From the result of enantioseparation, ibuprofen and indoprofen achieved the better resolution than ketoprofen and fenoprofen due to their favorable orientation to fit into the β-CD-BIMOTs cavity. This orientation was depending on the structure of NSAIDs.